Characteristics of Operative Shoulder Injuries in the National Collegiate Athletic Association, 2009-2010 Through 2013-2014. Issue 8 (14th August 2018) - Gil, Joseph A.; Goodman, Avi D.; DeFroda, Steven F.; Owens, Brett D.
Background: Injuries to the upper extremity among collegiate athletes are reported to account for approximately 20% of all injuries; however, little is known about the proportion of these injuries that require surgery. Purpose/Hypothesis: The purpose of this study was to examine all shoulder injuries that required a surgical intervention and were recorded in the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP). We hypothesized that contact would be the mechanism causing injuries most at risk for needing surgery and that dislocations would be the injuries most likely to require an operative intervention. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Injury surveillance data between 2009-2010 and 2013-2014 for operative collegiate shoulder injuries and their associated sport exposures were analyzed. Results: A total of 185 operative shoulder injuries occurred over 3, 739, 004 athlete-exposures (AEs), for an overall incidence of 0.49 per 10, 000 AEs. The sports with the highest incidence of operative injuries were men's football (1.31/10, 000 AEs), men's wrestling (1.14/10, 000 AEs), men's ice hockey (0.60/10, 000 AEs), women's gymnastics (0.44/10, 000 AEs), and men's swimming (0.41/10, 000 AEs). Men were significantly more likely than women to sustain operative injuries for all sports combined. Of the injuries that required surgical treatment, superior labrum from anterior to posterior (SLAP) tears (46.4%), other non-SLAP glenoid labrum tears (46.2%), anterior shoulder dislocations (33.3%), and posterior shoulder dislocations (30.0%) were seen most often. There was no significant difference in injury proportion ratios (IPRs) for injuries requiring surgery when comparing contact versus noncontact mechanisms of injury (IPR, 1.0 [95% CI, 0.6-1.6]). The incidence of operative injuries sustained during competition was significantly higher compared with during practice. Conclusion: The sports with the highest incidence of operative shoulder injuries were men's football, men's wrestling, men's ice hockey, and women's gymnastics. Operative shoulder injuries were more likely to occur during competition. SLAP tears, other non-SLAP glenoid labrum tears, and anterior shoulder dislocations had the highest incidence of requiring surgery. Athletes sustaining these injuries, along with their coaches and medical providers, may benefit from identifying collegiate sport participants who are at highest risk for sustaining an operative injury. This may assist in planning medical care and setting expectations, which may be critical to a young athlete's career.